Challenges in Building an Institutional Research Data Catalogue - Sally Rumsey; Neil Jefferies (International Journal of Digital Curation, 2013)
The University of Oxford is preparing systems and services to enable members of the university to manage research data produced by its scholars. Much of the work has been carried out under the Jisc-funded Damaro project. This project draws together existing nascent services, adds new systems and services to ‘fill the gaps’ and provides a wide-ranging infrastructure. Development comprises four parallel strands: endorsement of a university research data management policy; training and guidance in research data management; technical infrastructure; and future sustainability. A key element of the technical infrastructure is DataFinder, a catalogue of Oxford research data outputs. DataFinder’s core purposes are to record the existence of Oxford datasets, enable their discovery, and provide details of their location. DataFinder will record metadata about Oxford research data, irrespective of location, discipline or format, and is viewed by the university as a crucial hub for the university’s Research Data Management (RDM) infrastructure.